Head-up Position did not Correlated with the Recovery Time of Lower Extremity Motor Function in Spinal Anesthesia Patiens - Arif, Taufan; Hamarno, Rudi; Bharata, Bisma Surya; Bachtiar, Arief (Journal of Ners and Midwifery, 2025)
Patients who are delayed in recovery after spinal anesthesia will be transferred to the post anesthesia care unit (PACU) which can lead to increased service costs and patient dissatisfaction. Lower extremity motor function recovery time after spinal anesthesia is the time it takes for patients to be able to move from the recovery room to the patient's original room. The purpose of this study was to determine the correlation of Head-up position to the recovery time of lower extremity motor function in spinal anesthesia patients in the recovery room. The design of the study was correlation with a “cross-sectional” approach. The population was post-spinal anesthesia patients in the recovery room who meet the criteria. The study used "purposive sampling" with 96 post-spinal anesthesia patients. The independent variable was the head-up position, while the dependent variable was the recovery time of lower extremity motor function. The analysis test used the Pearson correlation test. The results of the correlation test showed no correlation between head-up position and recovery time of lower extremity motor function in spinal anesthesia patients with p-value = 0.099 (>0.05). This was due to the longer the duration of surgery, the faster the effect of spinal anesthesia drugs will run out. It is recommended to apply the results of this study as a review of SOPs related to the intervention of giving a head-up position to post-spinal anesthesia patients in the recovery room.